THEORETICAL AND PRACTICAL TESTS IN ALL-RUSSIAN SCHOOL PHYSICAL EDUCATION OLYMPIAD - Raizikh, A.A.; Maksimova, S.S.; Alabuzhev, A.E. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to analyze progress of the theoretical and practical test system for the school and municipal qualifiers for the All-Russian School Physical Education Olympiad. Methods and structure of the study. The School Physical Education Olympiad theoretical and practical tests structure and contents are designed to test the competitors’ theoretical competency and skills by combinations of highly challenging tests. The winners need to demonstrate excellent physical fitness standards and skills supported by a profound knowledge of the modern physical education theory within the school syllabus. The theoretical and practical tests are updated in contents and difficulty levels on an annual basis as provided by the guidelines of the Central School Education Methodology Commission. The competitors are tested by responses to a set of standard questions that test their knowledge and skills in the most difficult domains of the primary and secondary school Physical Education materials [2, 4]. Results and conclusion. The School Physical Education Olympiads in the Udmurt Republic have accumulated vast organizational and management experience and knowledge to effectively vary the theoretical and practical tests contents and focuses, plus fair scoring, ranking and winner nomination systems.